The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jor.24531
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanics of subscapularis repair in reverse shoulder arthroplasty: The effect of lateralization and insertion site

Abstract: Functional outcomes of subscapularis (SSc) repair following reverse shoulder arthroplasty (RSA) remains controversial. SSc repair in combination with glenosphere lateralization was reported to yield worse clinical outcomes compared with the non‐lateralized glenosphere. The aim of this biomechanical study was to investigate how glenosphere lateralization and different re‐insertion sites can affect the biomechanics of the SSc after RSA. Nine patient‐specific RSA shoulder models were created from patients' comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Improving active and passive internal rotation after RTSA has been the focus of various biomelc hanica 1,2,4,6,14,16,19,20,[22][23][24][25][26][27]30,32,33,43,45 and clinical 5,21,[35][36][37]39,42,44 studies. The most important finding of our study is that active extension of at least 40 is a prerequisite for satisfactory fIR after RTSA.…”
Section: Discussionmentioning
confidence: 99%
“…Improving active and passive internal rotation after RTSA has been the focus of various biomelc hanica 1,2,4,6,14,16,19,20,[22][23][24][25][26][27]30,32,33,43,45 and clinical 5,21,[35][36][37]39,42,44 studies. The most important finding of our study is that active extension of at least 40 is a prerequisite for satisfactory fIR after RTSA.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The subscapularis tendon Biomechanic and functional implications of subscapularis tendon repair have been investigated thoroughly in patients treated with reverse total shoulder arthroplasty. [18][19][20] Whether to repair the subscapularis tendon or not remains an interesting topic in the field of reverse total shoulder arthroplasty. Friedman et al reported excellent outcomes after RTSA for both patients with and without subscapularis repair with a follow-up comparable to this present study.…”
Section: Functional Scoresmentioning
confidence: 99%
“…Computational modeling of RTSA facilitates estimation of muscle and joint loading, which is currently impossible to measure non-invasively in vivo. Modeling and simulation of RTSA has played a critical role in guiding implant positioning and surgical technique [19][20][21][22], prosthesis selection [23,24], implant design [25,26], and post-operative rehabilitation prescription [27,28]. To date, most modeling and simulation tools require high levels of expertise and are generally restricted to the research setting.…”
Section: Computational Modeling Techniquesmentioning
confidence: 99%
“…For example, shoulder muscle forces during upper limb elevation can be calculated in several minutes using a subject-specific rigid body model (Figure 1A) [28,31]; however, since deformation mechanics is neglected, the internal stresses and strains in the bone and implant cannot be accurately evaluated using this method. An important utility of rigid body models has been in their capacity to estimate the influence of arthroplasty on muscle moment arms, muscle and joint forces, and range of motion (ROM) at the shoulder, which are primary indicators of implant functional performance [21,23,24,[29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Computational Modeling Techniquesmentioning
confidence: 99%